2021
DOI: 10.3390/ijerph18020540
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Levels of Stress Perception, Experiencing Depressive Symptoms and Health-Related Quality of Life of Residents after the 2016 Gyeongju Earthquake

Abstract: Background: The aim of this study was to evaluate the impact of the 2016 Gyeongju Earthquake on the stress perception, depressive symptoms, and health-related quality of life (HRQoL) among Gyeongju residents. Methods: This study was a secondary analysis of the 2015–2017 Korean Community Health Survey undertaken in the disaster area, Gyeongju, and in controlled areas, Sangju and Yangju, which had varying seismic intensities. Pearson’s chi-square test, ANCOVA and two-way ANOVA were performed. Results: The stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Evidence has shown that the levels of psychological stress tend to be increased by unpredictable environmental factors such as natural disasters and the outbreak of deadly epidemics ( Han et al, 2021 ; Pickering, 2001 ; Yu et al, 2005 ). This is in line with our results emphasizing the significant relation between the pandemic events and the perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that the levels of psychological stress tend to be increased by unpredictable environmental factors such as natural disasters and the outbreak of deadly epidemics ( Han et al, 2021 ; Pickering, 2001 ; Yu et al, 2005 ). This is in line with our results emphasizing the significant relation between the pandemic events and the perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, after an earthquake, an entire population can be evacuated and the government can declare a state of emergency, leading to a considerable number of people requiring assistance in the following months (D'Alfonso et al, 2012). Therefore, natural catastrophes typically represent a source of intense psychological stress (Han et al, 2021; Itoh et al, 2022; Kotozaki & Kawashima, 2012; Lugović‐Mihić et al, 2021; Mondal et al, 2013; North & Pfefferbaum, 2013; Wakashima et al, 2019).…”
Section: Introductionmentioning
confidence: 99%